Effects of light and nutrients on intraspecific competition among midges from a shallow eutrophic lake. (13th March 2021) - Wetzel, Rebecca L.; McCormick, Amanda R.; Phillips, Joseph S.; Ives, Anthony R.
Abstract : 1. Intraspecific competition for food may affect the development, survival, and fecundity of organisms. However, environmental variation in abiotic conditions can influence resource quality and/or quantity, thereby modifying the strength of intraspecific competition. 2. This study focuses on intraspecific competition among Tanytarsus gracilentus (Chironomidae: Diptera) larvae. In Lake Mývatn, Iceland, T. gracilentus undergoes large population fluctuations, and evidence suggests that these fluctuations are governed by consumer‐resource interactions between the larvae and benthic diatoms. In two experiments, we studied (i) the effects of larval density on individual development and survival, and (ii) how light and nutrients (nitrogen and phosphorus) mediate the strength of intraspecific competition across a density gradient. 3. Survival declined with increasing larval density in both experiments, although not significantly in the first experiment in which we manipulated only density. In the second experiment, enhancement of either light or phosphorus mitigated the negative effect of larval density on survival. In both experiments, density had a negative effect on individual development. In the first experiment, fewer larvae progressed to the final fourth instar at higher densities. In the second experiment, larvae were smaller in high density treatments, and this effect was most pronounced in the treatments without light or phosphorus supplementation. 4. These results highlight the potential for environmental factors to influence the strength of density‐dependent competition. Environmental variation that affects resource quantity or quality may influence the overall dynamics of our study organism and other populations whose dynamics are controlled by consumer‐resource relationships. Abstract : Characterising the effect of environmental factors on the strength of intraspecific competition is essential for efforts to understand the mechanisms of population regulation in variable environments. We explored how light, nitrogen, and phosphorus enrichment influence the strength of intraspecific competition among the aquatic larvae of the midge T. gracilentus in two laboratory experiments. Our results show that elevated light and phosphorus ameliorated the negative effect of competition on survival and body size.